Managing rice fallow lands of the Eastern Indian Himalayas: Impacts of residue management and varietal interventions on soil properties, carbon stocks, and productivity. (24th October 2021) - Layek, Jayanta; Das, Anup; Ramkrushna, Gandhiji Idapuganti; Krishnappa, Rangappa; Ghosh, Probir Kumar; Lal, Rattan; Choudhury, Burhan Uddin; Mohapatra, Kamal Prasad; Babu, Subhash; Yadav, Gulab Singh; Dey, Utpal
Abstract: Degenerating soil properties, low diversification, and productivity are the major issues for keeping large areas as fallow after rainy season rice ( Oryza sativa L.) in Southeast Asia. Long‐duration rice cultivars along with conventional till farming and lack of irrigation facilities limit the chances of growing succeeding crops like pulses in rice fallow areas. Therefore, a field study was conducted to test the hypothesis that cultivating short‐duration rice and lentil ( Lens culinaris Medic.) cultivars along with residue retention through mulching or standing rice stubble under no‐till (NT) farming for lentil can enhance the productivity in rice fallow areas and improve economic returns from the cropping system by conserving soil moisture and improving soil properties and carbon stocks. Two rice cultivars (namely, Shahsarang‐1: high yielding and medium duration; and Mendri: local, low yielding, and long‐duration variety), two high biomass lentil varieties (DPL‐81: early duration and IPL‐406: medium duration), and three rice residue management practices (namely, residue removal, 20 cm standing stubble, and mulching at 5 Mg ha −1 in lentil) were tested in the rice–lentil system. After harvest of rainy season rice, lentil was sown under NT using a manually operated furrow opener. Results of a 3‐year study revealed that rice residue retention as mulch at 5 Mg ha −1 and 20 cm standing stubbles (~2 Mg ha −1 ) conserved residual soil moisture and recorded significantly lower bulk density (1.10 and 1.09 Mg m −3 ), increased water‐holding capacity (57.05% and 55.14%), and improved water infiltration rate (3.47 and 3.30 cm hr −1 ) compared to residue removal. Soil organic carbon (SOC), soil microbial biomass carbon, dehydrogenase enzyme activity, available nitrogen, and phosphorus contents at 0–15 cm soil depth were significantly higher by 7.2%–11.1%, 3.9%–6.8%, 4.1%–6.7%, 2.7%–6.4%, and 2.7%–8.0%, respectively, under standing rice stubbles/mulching than residue removal. The SOC stock (25.3 Mg ha ‐1 ) under mulching was significantly higher than that recorded under residue removal at 0–15 cm (23.4 Mg ha −1 ) and remained non‐significant at 15–30 cm depth. A significantly higher mean seed yield of lentil was obtained under mulching (1.68 Mg ha −1 ) and standing stubbles (1.49 Mg ha −1 ) than that under removal (1.27 Mg ha −1 ). Average productivity of lentil (1.53 Mg ha −1 ) after medium‐duration rice variety Shahsarang‐1 was greater than that grown after local long‐duration rice variety Mendri (1.43 Mg ha −1 ). The mean seed yield of early lentil variety DPL‐81 grown after medium‐duration rice was significantly higher (1.60 Mg ha −1 ) than medium‐duration lentil variety IPL‐406 (1.36 Mg ha −1 ). Thus, cultivating medium‐duration rice (Shahsarang‐1) followed by early‐duration lentil variety (DPL‐81) and rice residue retention either through mulching or standing rice stubble is recommended for improving soil properties, carbon stock, and productivity of lentil in rice fallow areas of the Eastern Himalayan region of India and other similar agro‐ecosystems.